A game-to-game investigation of the relation between need-supportive and need-thwarting coaching and moral behavior in soccer. (July 2017) - Delrue, Jochen; Vansteenkiste, Maarten; Mouratidis, Athanasios; Gevaert, Kimberly; Vande Broek, Gert; Haerens, Leen
Abstract: Objective: Although perceived need-supportive and need-thwarting coaching have received considerable attention, the question whether coach behavior fluctuates from game to game, with resulting associations with players' moral behavior has not been examined. Design and method: A Belgian sample of soccer players ( N = 197; M = 26.57) was followed during five competition games, with players completing measures both prior to and following each game assessing, pre-game and on-game perceived coaching as well as athletes' moral behavior. Results: Results of multilevel analyses indicated that there exists substantial variation in perceived need-thwarting and need-supportive coaching behavior from game to game. The game-to-game variation in perceived pre-game need-thwarting coaching behavior related positively to variation in the adoption of an objectifying stance, which, in turn, related to variation in antisocial behavior oriented towards the opponent, the referee, and even their own teammates. Variation in perceived on-game need-supportive and need-thwarting coaching behavior yielded an additional relation to team-related moral outcomes. Finally, supplementary analysis indicated that these effects also held for an objective marker of moral functioning (i.e., number of yellow cards) and that players' level of competition-contingent pay related to their antisocial behavior via an objectifying stance. Conclusion: The discussion highlights the fluctuating and dynamic nature of motivating coaching behavior, and its association with players' moral functioning. Highlights: Variation from game to game in (de)motivating coaching behavior is found. This variation goes along with variation in players' moral behavior during the game. Coaching behavior before the game influences players' behavior towards opponent and referee. Coaching behavior during the game influences players' behavior towards own teammates.